2018
DOI: 10.1080/09602011.2018.1502672
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to virtual prisms and its relevance for neglect rehabilitation: a single-blind dose-response study with healthy participants

Abstract: Prism adaptation (PA) has been applied with mixed success as a rehabilitation method of spatial neglect. Results from many single-case and multiple case studies as well as randomised controlled trials do not produce a clear picture of the efficacy of PA. We here tested a new method of PA, by inducing adaptation effects in the virtual reality. Healthy participants were attributed to one of four groups: no deviation, 10-, 20-, or 30-degrees rightward deviation. In contrast to classical wedge prisms, we induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…[94][95][96][97] A possible explanation of negative findings might be that visuomotor adaptation (ie, aftereffect) has to reach a critical threshold to affect performance in other tasks. 98 Given the high intra-and interindividual variability of individuals with USN, visuomotor adaptation induced by low power prisms (i.e., shifting the visual field of 5°, 6°or 10°)as those used in RCT studies that did not find any beneficial outcomes after PA [94][95][96][97] might be too small to produce detectable effects in all patients. The fact that the critical threshold can only be reached with prisms of high power (i.e., shifting the visual field of 10°or 12°, as those used in the above studies that found significant PA effects) might explain some negative findings.…”
Section: Prismatic Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…[94][95][96][97] A possible explanation of negative findings might be that visuomotor adaptation (ie, aftereffect) has to reach a critical threshold to affect performance in other tasks. 98 Given the high intra-and interindividual variability of individuals with USN, visuomotor adaptation induced by low power prisms (i.e., shifting the visual field of 5°, 6°or 10°)as those used in RCT studies that did not find any beneficial outcomes after PA [94][95][96][97] might be too small to produce detectable effects in all patients. The fact that the critical threshold can only be reached with prisms of high power (i.e., shifting the visual field of 10°or 12°, as those used in the above studies that found significant PA effects) might explain some negative findings.…”
Section: Prismatic Adaptationmentioning
confidence: 99%
“…144 A final promising protocol was tested in a single-blind dose-response study in healthy subjects, by using VR as an alternative to real prisms. 98 Authors progressively induced a displacement of the visual field following the virtual PA procedure, making difficult for the subject to become aware of the experimental manipulation. Results showed that large rightward deviations may affect sensorimotor performance in healthy participants similarly to neglect patients without generating discomfort linked to the large visual shift.…”
Section: Virtual Realitymentioning
confidence: 99%
“…During VPAT mode, the behavioral adaptation during pointing was observed according to the degree of virtual hand deviation (Fig 6). In recent studies with a VPAT system using HMD and a hand-held controller, healthy adults or stroke patients with USN showed clear post-VPAT adaptations in open-loop pointing (Gammeri et al 2020;Bourgeois et al 2021). The pointing errors in post-VPAT adaptation at 20° deviation was about 8° in healthy adults (Gammeri et al 2020), and that after 15° deviation VPAT was 4.4° in stroke patients with USN (Bourgeois et al 2021), similar to our study (8.48°).…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies evaluated the transfer effect of VPAT using bisection, landmark or cancellation tasks but their results were contradictory (Gammeri et al 2020;Bourgeois et al 2021). The transfer effect was observed after 30° VPAT adaptation in healthy adults (Gammeri et al 2020), but not in the cross-over study among stroke patients with USN (Bourgeois et al 2021). We think that the negative results of VPAT in the study by Bourgeois et al (Bourgeois et al 2021) with stroke patients should be cautiously interpreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation